A RARE CASE OF TRIFOCAL RADIUS FRACTURE - Ting Chung, Lim; Faris Indra Prahasta, Didi Indra; Mohd Anuar Ramdhan, Ibrahim (JUMMEC, 2023)
Trifocal fracture of a radius is a rare injury. Trifocal factures involving the shaft of a radius were previously mentionedin a few literature. This type of fractures, involving proximal, shaft, and distal radius with ulna shaft fracture, hasalso been reported once. However, to the best of our knowledge, our report is the first describing trifocal injuriesaffecting the shaft and proximal and distal intraarticular part of the radius with an intact ulna shaft. Thorough clinicaland radiological assessments are necessary for diagnosis as these injuries are commonly missed. We would like toshare the presentation of this rare case and the importance of the correct management to achieve a good outcome.